SCREENING OF STAPHYLOCOCCUS AUREUS ISOLATES FROM MASTITIS FOR ANTIBACTERIAL SUSCEPTIBILITY PATTERN AND BETALACTAMASE PRODUCTION - S.Pavulraj; S.Amsaveni; L. Kalaiselvi; S.Ramesh (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Isolates of Staphylococcus aureus from bovine clinical and subclinical mastitis were tested for ß-lactamase production and antimicrobial susceptibility pattern. Beta-lactamase production was assessed by penicillin-phenol red acidometric test. Antimicrobial susceptibility was tested by measuring MIC by Resazurin dye broth microdilution method. Forty per cent of isolates tested were positive for â-lactamase production. The susceptibility of S. aureus isolates were:  gentamicin (100%), enrofloxacin (70%), rifampin (70%) and tetracycline (40%). Complete resistance was observed for amoxycillin, ceftriaxone, nalidixic acid, erythromycin, sulphamethoxazole and trimethoprim. The results of the study indicate the widespread resistance of Staphylococcus aureus isolates against commonly used antimicrobials and also the utility of resazurin test and ß-lactamase test to study antimicrobial drug resistance.